EnGENDERing One Health and addressing gender gaps in Infectious disease control and response: Developing a Gender, One Health and Emerging Pandemics threat short course for the public health workforce in Africa. - Amuguni, Janetrix Hellen; Mugisha, Anthony; Kyewalabye, Elizabeth; Bagnol, Brigitte; Talmage, Roberta; Bikaako, Winnie; Naigaga, Irene (Advances in Social Sciences Research Journal, 2018)
Most capacity building efforts to investigate and counter emerging infectious diseases have focused on supporting public health agencies. However, to improve the understanding of the epidemiology, and outcome of diseases, aid in their detection and treatment and increase public participation in prevention and control, gender roles must be considered. Gender plays a significant role in shaping infectious disease response. In the most recent Ebola Outbreak in the West African region, glaring gender disparities were apparent as Ebola spread through nations decimating families. Policy implementers, practitioners and researchers were slow to recognize the gender implications, ask why, and build responses accordingly. A report that examined the avian influenza crisis in South East Asia in 2008 concluded that women were clearly in the frontline defense against the disease both as caretakers of the poultry and the families, and yet strategies to combat avian influenza did not consider their roles and potential contribution to the prevention and response. Makerere University, Uganda with the support of Tufts University developed a Gender, One Health and Infectious Disease short course that allows public health specialists to address gender gaps, and explore how gender, the realm of emerging pandemic threats and One Health intersect and how policies can be developed and/or implemented to address those gaps. The week long short course targets in service personnel in multiple disciplines, the private sector, faculty and students from OHCEA institutions and Africa. The course themes apply gender analysis tools to disease surveillance, response, and control and address gender sensitive emergency response planning.